Diversitas dan Distribusi Plankton di Perairan Tambak Kabupaten Tuban Propinsi Jawa Timur - Machluddin Amin; Utojo Utojo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
This study was aimed to know diversity and distributionof plankton in the brachkishwater pond of Tuban Regency, East Java Province. Sampling of plankton was conducted in the intensive and extensive pond with to filter of water sample of 100 L to be 100 mL used of plankton net number 25. Parameters wich observed : amount of genera and individu of plankton, and index of plankton (diversity, an variability dan dominance). The results showed that diversity of plankton in intensive and extensive pond, each 13 and 11 genera and the distrbution 6,316 and 157 ind/L. Stability condition of plankton in the intensive and extensive pond, both had an variability wich un constant, but had variability and dominance the constant.